2015
DOI: 10.1103/physrevb.92.195130
|View full text |Cite
|
Sign up to set email alerts
|

Angle-dependent magnetoresistance oscillations of cuprate superconductors in a model with Fermi surface reconstruction and magnetic breakdown

Abstract: We calculate angle-dependent magnetoresistance oscillations (AMRO) for interlayer transport of cuprate superconductors in the presence of (π, π) order. The order reconstructs the Fermi surface, creating magnetic breakdown junctions; we show how such magnetic breakdown effects can be incorporated into calculations of interlayer conductivity for this system. We successfully fit experimental data with our model, and these fits suggest a connection between (π, π) order and the anisotropic scattering observed in ov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…The inset in Fig. 2a shows the dependence of the magnetoresistance on magnetic field orientation (angle-dependent magnetoresistance (ADMR) is a powerful tool for investigating the geometry of the quasi-particle dispersion, yielding, for example, detailed information about the Fermi surfaces of high T c superconductors 30 ), at 1.4 K (well into the low-temperature regime) and 4.2 K (in the intermediate temperature regime). The significant change in the form of the ADMR is characteristic of the transition from bulk-dominated conduction at high temperatures to surface-dominated conduction at 1.4 K.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The inset in Fig. 2a shows the dependence of the magnetoresistance on magnetic field orientation (angle-dependent magnetoresistance (ADMR) is a powerful tool for investigating the geometry of the quasi-particle dispersion, yielding, for example, detailed information about the Fermi surfaces of high T c superconductors 30 ), at 1.4 K (well into the low-temperature regime) and 4.2 K (in the intermediate temperature regime). The significant change in the form of the ADMR is characteristic of the transition from bulk-dominated conduction at high temperatures to surface-dominated conduction at 1.4 K.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…where j indexes all of the MB junctions, n j indicates the number of times the quasiparticle has Bragg diffracted at the j th MB junction, and ∆k (j) z is the amount by which k 0 z changes when undergoing Bragg diffraction at the j th MB junction; ∆k (j) z can be found through simple geometric means, as described in Ref. 23. We set n j (ϕ 0 ) = 0.…”
Section: Calculating Interlayer Admrmentioning
confidence: 99%
“…Building on Falicov and Sievert's treatment of magnetic breakdown for in-plane conductivity 25 , Nowojewski et al showed that this issue can be solved by writing a self-consistent, vectorized form of the Shockley-Chambers tube integral 26,27 . This method has previously been used to study systems wherein ω did not vary with ϕ 23,28 . For this work, we extend the equations of Ref.…”
Section: B Fermi Surface Across the Brillouin Zone Boundarymentioning
confidence: 99%
See 2 more Smart Citations